2016
DOI: 10.1095/biolreprod.116.138958
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Coumestrol on Progesterone and Prostaglandin Production in the Mare: In Vitro and In Vivo Studies

Abstract: Coumestrol (Cou) is a plant-derived phytoestrogen that induces various pathologies in the female reproductive tract. Although effects of phytoestrogens on reproductive function in other species are well documented, their influence on progesterone (P) and prostaglandin (PG) secretion in the mare is unknown. The aim of this study was to determine if Cou directly affects P and PG concentrations (in vivo) and endometrial PG secretion (in vitro) in the mare. In experiment 1, the mares (n = 4) were fed for 14 days o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Even though analysis identified a broad range of phytoestrogens in the pasture samples consumed, the results of the samplings were inconclusive. Subsequent research comparing mares to cows and ewes identified that mares may also experience temporary infertility, in some instances as rapidly as 14 days following lucerne ingestion [ 74 ]. After exposure to lucerne for a minimum of 14 days, lack of ovulation, uterine edema and fluid accumulation were recorded in all eight mares in the trial ( Figure 7 ) [ 74 ].…”
Section: Effects On Female Reproductive Physiologymentioning
confidence: 99%
See 4 more Smart Citations
“…Even though analysis identified a broad range of phytoestrogens in the pasture samples consumed, the results of the samplings were inconclusive. Subsequent research comparing mares to cows and ewes identified that mares may also experience temporary infertility, in some instances as rapidly as 14 days following lucerne ingestion [ 74 ]. After exposure to lucerne for a minimum of 14 days, lack of ovulation, uterine edema and fluid accumulation were recorded in all eight mares in the trial ( Figure 7 ) [ 74 ].…”
Section: Effects On Female Reproductive Physiologymentioning
confidence: 99%
“…Subsequent research comparing mares to cows and ewes identified that mares may also experience temporary infertility, in some instances as rapidly as 14 days following lucerne ingestion [ 74 ]. After exposure to lucerne for a minimum of 14 days, lack of ovulation, uterine edema and fluid accumulation were recorded in all eight mares in the trial ( Figure 7 ) [ 74 ]. Ferreira-Dias et al [ 31 ] also observed uterine edema and persistent anovulatory follicles in mares fed on a lucerne diet.…”
Section: Effects On Female Reproductive Physiologymentioning
confidence: 99%
See 3 more Smart Citations